Oh, Sport! Are You Peace? (About Different Kinds of Sports Media Discourse) - Kazimianec, Jelena (Respectus Philologicus, 2015)
The ways of description and interpretation of such socially meaningful event as the World Football Championship 2014 are considered in this article. The author justifies the importance of choosing a sports topic and in particular football in the modern world, showing that first of all the sports discourse is a journalistic discourse. That is why the ways of the representation and description of sports events are the basic means for creating its concept. The author has chosen one day of the World Football Championship 2014 for the analysis to show that not the sports events, but the acts of violence accompanying them are becoming the basic subject matter of the description. In relation to this, the author suggests to speak about a special type of sports discourse: a discourse of sports aggression. Its main features are: special lexical stock phrases, inaccuracy in the supply of information, lack of logic in the description of events, and expressiveness of the means used to describe the acts of violence. The author comes to the conclusion that it is difficult to make the precise cognitive diagram of the sport event reading due to the additional information, as the reader’s attention in such messages is focused only on the description of the details, which are connected with the facts of aggression that occurred in the sport action. The modern sports appear as the catalyst of aggressive actions instead of initiating the peace.